PENGARUH PERSONAL BRANDING GURU PPKn TERHADAP MOTIVASI BELAJAR SISWA SMA NEGERI 1 KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Heppy Hariansing; Supentri; Sri Erlinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teachers are still minimally familiar with Personal Branding in building teacher profiles, in general teachers still imitate the same patterns as other teachers so they do not show a Personality that distinguishes them from other teachers. The next phenomenon is the lack of strategy in marketing content, content is one of the important elements in building Personal Branding, in an era full of technological advances like this internet access is very easy to find so it is important for teachers to be able to utilize this in building Personal Branding, the content in question is not only limited to videos or sharing information via the internet but can also be a motivator for students so that it becomes an added value for teachers this will make the view of students that a teacher must be a motivator and will motivate students especially in learning motivation. The purpose of this study is to determine the Effect of Personal Branding of PPKn Teachers on Student Learning Motivation at SMA Negeri 1 Kuantan Hilir Seberang, Kuantan Singingi Regency. This research will be conducted using a survey method with a descriptive quantitative approach. Quantitative descriptive research is research that describes variables as they are supported by data in the form of numbers generated from actual conditions. The data collection methods used were observation, questionnaires, documentation, and interviews. The Personal Branding of PPKn Teachers (Variable X) was categorized as Very Good. This can be seen in the average recapitulation of the percentage of student respondents as many as (30.47%) answered "Very High", as many as (63.52%) answered "High", and as many as (5.63%) answered "Not High" and as many as (0.2%) answered "Very Not High".